RURAL-URBAN DISPARITY OF CONDOM USE AT THE LAST SEX AMONG INDONESIAN MALE ADOLESCENTS - Fadhaa Aditya Kautsar Murti; Kencana Sari (JURNAL KESEHATAN REPRODUKSI, 2023)
Introduction: Several studies has established the urgency to use condom, however in Indonesia, condom use remains low and the gap is more distinct in different living setting. Since condom at the last sex is a predictor for frequency due to its recency, this research aims to understand condom use at the last sex. Methods: This study uses data from Indonesian Demographic Health Survey (IDHS) 2017, the latest survey to capture sexual behaviour. The population for this study is Indonesian male adolescents. The data is analysed using logistics regression using complex-sample approach. In addressing the disparity, this research will separate the result according to rural-urban areas. Results: Internet use is associated with condom use at the last sex for adolescents in rural areas (p-value= 0.013, aOR= 3.851 (1.332—11.128)). Age (p-value= 0.005, aOR= 2.004 (1.232—3.257)), education (p-value= 0.001, aOR= 2.672 (1.493—4.784)), and read newspaper/magazine (p-value= 0.044, a0R= 0.449 (0.238—0.847) and 0.669 (0.405—1.106)) are associated with condom use at the last sex for adolescents in urban areas. Attitude towards condom use is found to be significant in both living setting (p-values= 0.03, a0R= 4.360 (1.661—11.446) for rural areas and p-values= 0.011, aOR= 2.058 (1.184—3.576) for urban areas) and acts as the strongest predictor in both rural-urban areas. Conclusion: Further intervention should address the disparity of rural-urban areas and taking mass media consumption, age, and education into an account as well as shaping a better attitude towards condom.